Dokumentasi Peningkatan Wawasan Masyarakat Melalui Media Online Dinas KOMINFO Kabupaten Tangerang - Wahyu Hidayat; Desy Apriani; Dwi Setiadi (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
Nowadays it is very important to the wider community. With the information everyone will know. This Video documentation is designed to explain the work program of the Tangerang District government that synergize with the Indonesian National Armed Forces (TNI) in carrying out the village Manunggal Army Building (TMMD) program to 105. Research aims of the Department of Kominfo Tangerang Regency in delivering information and improving public insight about the government program of Tangerang Regency.